Transmission characteristics of air-ground channel in aerial communication platform - Xiaobin FU; Baohui ZHENG (Dianxin kexue)
Satellite communication can solve the problem of global communication,at the same time,it follows the problems of difficult deploy and limited satellite resources.Aerial communication platform is consisted of aircraft with payload communication and not more than 10 km from ground.The platform communicating with ground nodes can solve the weakness of traditional satellite communication.The loss of air-to-ground channel was analyzed to model the air-to-ground wideband channel in Ku and Ka band.The consequence of theory and simulation demonstrates that the fading of the model has serious influence on transmission performance.In low elevation transmission,the value of K-factor is small because of multipath reception.Simulation results show that orthogonal frequency division multiplexing (OFDM) can be a good candidate for wideband communications to transmit payload data from aerial platform to ground station.